The effect of the otago exercise program (OEP) on motor function in elderly people with osteoporosis - Lusi Noviyanti; Dilia Ananda Pratiwi (Malahayati International Journal of Nursing and Health Science, 2026)
Background: The number of elderly people in Indonesia continues to increase, with the proportion of the elderly population reaching 11.75% in 2023, up from 10.48% in the previous year. This increase in the elderly population is directly proportional to the prevalence of osteoporosis, which not only impacts individuals but also places a burden on families and the health system. Purpose: To analyze the effect of physical therapy on the balance of elderly people with osteoporosis, to assess changes in muscle strength after undergoing physical therapy and to identify the impact of physical therapy on the risk of falls in elderly people with osteoporosis. Method: This study employed a quantitative, quasi-experimental design with a pre-test and post-test design. Accidental sampling was used, and univariate analysis was used to determine the frequency distribution of each variable. Bivariate analysis used the Wilcoxon mean difference test for each group and the Mann-Whitney test to determine differences in post-test results between the two groups. Results: The majority of participants were aged ≥ 66 years, more female participants than male, most participants had jobs. • The average increase in BBS scores in the OEP group (2.67). The average decrease in TUG scores in the OEP group (0.87) was lower than the control group (2.00), p value = 0.0005. Both results are supported by a highly significant p value (<0.001) and a large effect size (>1), which means that the OEP intervention had a strong and real impact on elderly participants. Conclusion: Statistical analysis results indicate that the Otago Exercise Program (OEP) has a significant and significant impact on improving balance in older adults (BBS score), mobility, and reducing fall risk (TUG score). Therefore, the OEP is recommended as an effective physical exercise program to improve the quality of life in older adults and reduce the risk of falls. Suggestions: Involve a larger number of participants Extend the duration of the intervention program and conduct long-term follow-up, Include additional variables such as quality of life, actual fall risk, and the impact of the intervention on daily independence.